Evaluation of indirect pulp capping using three different materials: A randomized control trial using cone-beam computed tomography - Vijay Prakash Mathur; Jatinder Kaur Dhillon; Ajay Logani; Gauri Kalra (Wolters Kluwer Medknow Publications, 2016)
Objective: The objective of this study was to determine the most suitable material for indirect pulp treatment (IPT) clinically and to determine the thickness (in mm) and type of tissue in terms of radiodensity (in Hounsfield units [HU]) formed after pulp capping using cone-beam computed tomography (CBCT) scan. Materials and Methods: A longitudinal interventional single-blind randomized clinical trial was conducted on 94 children (7-12 years) with a deep carious lesion in one or more primary second molar and permanent first molar without the history of spontaneous pain indicated for indirect pulp capping (IPC) procedure. About 109 teeth were treated using three materials, namely, calcium hydroxide (setting type), glass ionomer cement (Type VII), and mineral trioxide aggregate randomly. The teeth were followed up at an interval of 8 weeks, 6 months, and 1 year for success of IPT as per the American Academy of Pediatric Dentistry clinical criteria. For determining the thickness and type of dentin tissue formed, a CBCT scan was done immediately postoperative and another scan at an interval of 6 months. The scans were compared to evaluate the average thickness of the dentin bridge formed. Results and Conclusions: Success rate for IPC was 96.85%. A significant difference was obtained in the average thickness of reparative dentin at immediate postoperative and 6-month postoperative values in all three groups suggesting distinct barrier formation. Similar significant findings were obtained in radiodensity of barrier formed (in HU). All three materials were found to be equally suitable as IPC agents suggesting mineral gain.